Harnessing solar and wind for sustainable cross-border electricity trade in the Greater Mekong Subregion - Do, Thang Nam; Burke, Paul J.; Lu, Bin (Frontiers in Environmental Science, 2023)
• Sustainable, low-emission electricity generation options are needed in the Greater Mekong Subregion, including for cross-border electricity trade • Large-scale investment in solar and wind power, together with off-river pumped hydro energy storage, is identified as a promising way forward • The GMS has many potential off-river pumped hydro sites that could provide ample energy storage • Actionable recommendations include greater use of bilateral power purchase agreements for cross-border solar and wind power supply, and potential development of a high-voltage direct current grid • Institutional prioritization and ongoing evaluation are required to ensure desired social, environmental, and economic outcomes from the transition.